Extreme static compression of carbon to terapascal pressures. (April 2019) - Wu, Hao; Luo, Xudong; Wen, Libin; Sun, Hong; Chen, Changfeng
Abstract: Recent reports of record-setting ultrahigh static pressures achieved in diamond anvil cells (DACs, 495 GPa) and double-stage DACs (ds-DACs, 1 TPa) raise fundamental questions about mechanical response of diamond and related carbon structures under extreme compression. Here we present results from a combined first-principles calculation and finite-element analysis that unveil the mechanisms responsible for the greatly enhanced compressive strengths of these carbon structures by lateral confining stresses concentrated near anvil tips, stemming from structural deformations in compressed DACs and further strengthened by additional confining pressures in ds-DACs. Our results indicate that diamond anvils oriented in the [001] direction with a flat culet diameter of 20 μm can sustain peak pressures above 500 GPa, vastly exceeding its pure compressive strength of about 200 GPa. Among nano-carbon structures with enhanced shear strengths by nano- or grain-boundaries, we find that nano-twinned diamond possesses the highest compressive strength, reaching 1 TPa in ds-DAC settings, in agreement with experimental observations. The present findings establish key benchmarks and expand the realm of understanding of diamond and related carbon structures under extreme loading conditions; these results offer crucial insights for rational design of advanced and novel DAC devices. Graphical abstract: Image 1